2020
DOI: 10.3390/s20216074
|View full text |Cite
|
Sign up to set email alerts
|

Human and Animal Motion Tracking Using Inertial Sensors

Abstract: Motion is key to health and wellbeing, something we are particularly aware of in times of lockdowns and restrictions on movement. Considering the motion of humans and animals as a biomarker of the performance of the neuro-musculoskeletal system, its analysis covers a large array of research fields, such as sports, equine science and clinical applications, but also innovative methods and workplace analysis. In this Special Issue of Sensors, we focused on human and animal motion-tracking using inertial sensors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 13 publications
(23 reference statements)
0
18
0
1
Order By: Relevance
“…Recently, other studies proposed an investigation into the protraction and retraction angles of horse limbs by the use of IMUs [ 12 , 15 , 24 ]. Inertial sensors, i.e., IMUs, are more versatile [ 28 ] and they can allow recordings in real equestrian conditions. However, they require the use of specific methods to estimate the spatial orientation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, other studies proposed an investigation into the protraction and retraction angles of horse limbs by the use of IMUs [ 12 , 15 , 24 ]. Inertial sensors, i.e., IMUs, are more versatile [ 28 ] and they can allow recordings in real equestrian conditions. However, they require the use of specific methods to estimate the spatial orientation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inertial sensors, i.e., IMUs, are more versatile [ 28 ] and they can allow recordings in real equestrian conditions. However, they require the use of specific methods to estimate the spatial orientation [ 28 ]. In this study, using a strapdown inertial navigation system approach [ 47 ], the orientation of the IMU positioned on the horse’s canon bone was computed by the integration of the gyrometer data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was demonstrated that inertial measurement units (IMUs) are a real alternative to performing motion capture [ 18 ]. The use of IMUs allows recording the horse locomotion with on-board technologies and in field conditions [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%